2023
DOI: 10.1186/s40246-023-00468-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin-10 gene polymorphisms (rs1800871, rs1800872, and rs1800896) and severity of infection in different SARS-CoV-2 variants

Abstract: Background Polymorphisms in the interleukin-10 (IL10) gene have been linked to the severity of the patients infected with the viral infections. This study aimed to assess if the IL10 gene polymorphisms rs1800871, rs1800872, and rs1800896 were linked to coronavirus disease 19 (COVID-19) mortality in different severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants in the Iranian population. Methods For genotyping IL10 rs1800871, rs1800… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…Our data is the first to unravel the association between polymorphisms in IL-10 gene promoter and COVID-19 in an Egyptian population, which gives insight into the genetic diversity of immune responses towards SARS-COV2. We provided complementary evidence to the role of TNFa-308 polymorphism in a different Egyptian population [ 20 ] and were consistent with findings in Iranian population [ 50 ]. In conclusion, this study sheds light on the genetic determinants influencireatment response, and clinical outcomes in SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 88%
“…Our data is the first to unravel the association between polymorphisms in IL-10 gene promoter and COVID-19 in an Egyptian population, which gives insight into the genetic diversity of immune responses towards SARS-COV2. We provided complementary evidence to the role of TNFa-308 polymorphism in a different Egyptian population [ 20 ] and were consistent with findings in Iranian population [ 50 ]. In conclusion, this study sheds light on the genetic determinants influencireatment response, and clinical outcomes in SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 88%
“…Concerning this issue, a previous study reported that polymorphisms in the IL10 gene are linked to the severity of the infected patients. This study found that IL10 gene polymorphisms rs1800871, rs1800872 and rs1800896 were linked to COVID-19 mortality in different SARS-CoV-2 variants in the Iranian population [41].…”
Section: Discussionmentioning
confidence: 66%
“…There is evidence supporting the role of inflammation in the acute COVID-19 phase [ 4 , 5 ] and also in the post-COVID phase [ 20 ]. Thus, several polymorphisms associated with inflammation have been related to severe COVID-19 illness in previous studies [ 7 , 8 , 9 , 10 ]. Our study did not find an association between four SNPs associated with severe COVID-19, e.g., IL-6 rs1800796 , IL-10 rs1800896 , TNF-α rs1800629 , and IFITM3 rs12252 , and the presence of long-lasting post-COVID symptoms more than one year after infection.…”
Section: Discussionmentioning
confidence: 99%
“…Different polymorphisms can account for the variability in expression of these pro-inflammatory cytokines [ 6 ]. For instance, genotyping of cytokine-related single-nucleotide polymorphisms (SNPs), e.g., IL-6 rs1800796 [ 7 ], IL-10 rs1800896 [ 8 ], TNF-α rs1800629 [ 9 ], and IFITM3 rs12252 [ 10 ], has shown them to underlie the differential viral virulence and severity of COVID-19. Looking at the research, most studies have investigated the potential role of SNPs at the acute phase of SARS-CoV-2 infection, focusing on the risk of developing the severe form of the COVID-19 illness [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation